Cangrelor inhibits the binding of the active metabolites of clopidogrel and prasugrel to P2Y12 receptors in vitro. (2nd April 2016) - Judge, Heather M.; Buckland, Robert J.; Jakubowski, Joseph A.; Storey, Robert F.
Abstract: Cangrelor is a rapid-acting, direct-binding, and reversible P2Y12 antagonist which has been studied for use during percutaneous coronary intervention (PCI) in patients with or without pretreatment with an oral P2Y12 antagonist. As cangrelor is administered intravenously, it is necessary to switch to an oral P2Y12 antagonist following PCI, such as the thienopyridines clopidogrel, and prasugrel or the non-pyridine ticagrelor. Previous studies have suggested a negative pharmacodynamic interaction between cangrelor and thienopyridines. This in vitro study evaluated the receptor-level interaction between cangrelor and the active metabolite (AM) of clopidogrel or prasugrel by assessing functional P2Y12 receptor number using a 33 P-2MeSADP binding assay. All P2Y12 antagonists studied resulted in strong P2Y12 receptor blockade (cangrelor: 93.6%; clopidogrel AM: 93.0%; prasugrel AM: 97.9%). Adding a thienopyridine AM in the presence of cangrelor strongly reduces P2Y12 receptor blockade by the AM (clopidogrel AM: 7%, prasugrel AM: 3.2%). The thienopyridine AMs had limited ability to compete with cangrelor for binding to P2Y12 (% P2Y12 receptor blockade after co-incubation with cangrelor 1000 nmol/L: 11.7% for clopidogrel AM 3 µmol/L; 34.1% for prasugrel AM 3 µmol/L). In conclusion, in vitro cangrelor strongly inhibits the binding of clopidogrel and prasugrel AMs to the P2Y12 receptor, consistent with the previous observation of a negative pharmacodynamic interaction. Care may need to be taken to not overlap exposure to thienopyridine AMs and cangrelor in order to reduce the risk of thrombotic complications following PCI.